Pengaruh Workplace Spirituality terhadap Komitmen Organisasi Karyawan BPRS Al Masoem Rancaekek - Rismawati Gustani; Agus Budiman (UNISBA Press, 2022)
Abstract. Human resources are an important part of achieving organizational goals, therefore it is necessary to produce good quality performance. Good quality and quantity of performance resulted from high organizational commitment. To increase organizational commitment, it can be through workplace spirituality. This study aims to examine the effect of Workplace Spirituality on the Organizational Commitment of the Employees of BPRS Al Masoem Rancaekek. This research method causality with the number of subjects 31 employees. This study uses a tool for measuring workplace spirituality from Ashmos and Duchon (2000) developed by Widyarini (2011), and a tool for measuring organizational commitment from Mowday, Steers, Porter (1979) developed by Tri Muji Ingarianti (2015). The analysis technique used is multiple regression analysis. The results of the study found that there was a positive influence of the workplace spirituality variable on organizational commitment by 33%. Where workplace spirituality has a high category of 68% and a high category of organizational commitment is 25.9%. Partially, the inner life component has an effect of 19.7%, the second order component of sense of community has an effect of 9.7%, and the meaningful work component has an effect of 3.6%. Abstrak. Sumber daya manusia merupakan bagian penting bagi tercapainya tujuan organisasi maka dari itu perlu menghasilkan kualitas kinerja yang baik. Kualitas dan kuantitas kinerja yang baik dihasilkan dari komitmen organisasi yang tinggi. Untuk meningkatkan komitmen organisasi dapat melalui workplace spirituality. Penelitian ini bertujuan untuk meneliti pengaruh Workplace Spirituality terhadap Komitmen Organisasi Karyawan BPRS Al Masoem Rancaekek. Metode penelitian ini kausalitas dengan jumlah subjek 31 Karyawan. Penelitian ini menggunakan alat ukur workplace spirituality dari Ashmos dan Duchon (2000) yang dikembangkan oleh Widyarini (2011), dan alat ukur komitmen organisasi dari Mowday, Steers, Porter (1979) yang dikembangkan oleh Tri Muji Ingarianti (2015). Teknik analisis pada yang digunakan adalah analisis regresi berganda. Hasil penelitian didapatkan bahwa terdapat pengaruh positif variabel workplace spirituality terhadap komitmen organisasi sebesar 33%. Dimana workplace spirituality berkategori tinggi sebanyak 68% dan Komitmen organisasi berkategori tinggi terdapat 25.9%. Secara parsial komponen inner life memberikan pengaruh sebesar 19.7%, urutan kedua komponen sense of community berpengaruh sebesar 9.7%, dan komponen meaningful work berpengaruh sebesar 3.6%.